Prevalence of prehypertension and its risk factors in midlife and late life: Indonesian family life survey 2014-2015 - Aida Lydia; Siti Setiati; Czeresna Heriawan Soejono; Rahmi Istanti; Jessica Marsigit; Muhammad Khifzhon Azwar (BMC, 2021)
Abstract Background Early detection of prehypertension is important to prevent hypertension-related complications, such as cardiovascular disease, cerebrovascular disease and all-cause mortality. Data regarding the prevalence of prehypertension among mid- and late-life population in Indonesia were lacking. It is crucial to obtain the prevalence data and identify the risk factors for prehypertension in Indonesia, which may differ from that of other countries. Methods The cross-sectional analysis utilized multicenter data from Indonesian Family Life Survey-5 (IFLS-5) from 13 provinces in 2014-2015. We included all subjects at mid-and late-life (aged ≥40 years old) from IFLS-5 with complete blood pressure data and excluded those with prior diagnosis of hypertension. Prehypertension was defined as high-normal blood pressure according to International Society of Hypertension (ISH) 2020 guideline (systolic 130-139 mmHg and/or diastolic 85-89 mmHg). Sociodemographic factors, chronic medical conditions, physical activity, waist circumference and nutritional status were taken into account. Statistical analyses included bivariate and multivariate analyses. Results There were 5874 subjects included. The prevalence of prehypertension among Indonesian adults aged > 40 years old was 32.5%. Age ≥ 60 years (adjusted OR 1.68, 95% CI 1.41-2.01, p <  0.001), male sex (adjusted OR 1.65, 95% CI 1.45-1.88, p <  0.001), overweight (adjusted OR 1.44, 95% CI 1.22-1.70, p <  0.001), obesity (adjusted OR 1.77, 95% CI 1.48-2.12, p <  0.001), and raised waist circumference (adjusted OR 1.32, 95% CI 1.11-1.56, p = 0.002) were the significant risk factors associated with prehypertension. Prehypertension was inversely associated with being underweight (adjusted OR 0.74, 95% CI 0.59-0.93, p = 0.009). Conclusions The prevalence of prehypertension in Indonesian mid- and late-life populations is 32.5%. Age ≥ 60 years, male sex, overweight, obesity, and raised waist circumference are risk factors for prehypertension.